Pengaruh Brand Awareness, Brand Loyalty, Dan Lini Produk Terhadap Keputusan Pembelian Merchandise Enhypen Di Toko Kpopconnection Jakarta Selatan - Lucyana Dewi; Rame Soekarsono (JAMBIS : Jurnal Administrasi Bisnis, 2022)
The greater the influence of K-wave in Indonesia, the greater the demand for products originating from South Korea. One such demand is on merchandise of K-pop idol groups. This study aims to determine and analyze the effect of brand awareness, brand loyalty, and product lines on purchase decisions both partially and simultaneously. The research method used was a quantitative method with data collection techniques in the form of questionnaire distribution. The population in this study were consumers who made purchases at the KpopConnection store in South Jakarta. The research sample consisted of 120 respondents who were selected using a non-probability sampling technique, i.e. incidental sampling, with the Slovin formula. The data obtained were then analyzed using linear regression technique with the help of SPSS version 25. The results of this study indicate that partially brand awareness affects purchase decisions by 59.8%, brand loyalty affects purchase decisions by 67.8%, and product lines affect purchase decisions by 59.5%; simultaneously brand awareness, brand loyalty, and product lines influence purchase decisions by 75.1%, with the remaining percentage being the influence of other factors outside this study.